1998
DOI: 10.1088/0031-8949/57/2/018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Axial Magnetic Fields on Backward Raman Scattering in Inhomogeneous Plasmas

Abstract: The effects of an axial magnetic field on the convective amplification and the threshold intensity of Raman backscattering instability in an underdense, inhomogeneous plasma is investigated. Two cases of incident pump wave were considered. For the R-circularly polarization case it is shown that the amplification factor increases with the magnetic field, it also increases with the plasma density while the threshold intensity decreases. For the L-circularly polarization case, it is shown that the amplification f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The expression for S 1,−3 can be obtained easily from Eq. (75) using the replacement rule 1 → 2, 2 → 1, 3 → −3, where the minus sign is interpreted using notations (21) and (22). Similarly, to obtain the expression for S 1,−2 , we can replace 1 → 3, 2 → 1, 3 → −2 in Eq.…”
Section: A Action Conservation Of On-shell Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression for S 1,−3 can be obtained easily from Eq. (75) using the replacement rule 1 → 2, 2 → 1, 3 → −3, where the minus sign is interpreted using notations (21) and (22). Similarly, to obtain the expression for S 1,−2 , we can replace 1 → 3, 2 → 1, 3 → −2 in Eq.…”
Section: A Action Conservation Of On-shell Equationsmentioning
confidence: 99%
“…where the minus sign in front of the second term comes from notation Eq. (22). Taking time derivative of the displacement operator, ∂ t (Π s ) is the velocity operator for species s, which is proportional to the current operator.…”
Section: Lagrangian Of Three-wave Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not unexplored territory. For instance, prior work studied how an external axial B field affects Raman backscattering in a hot, inhomogeneous plasma 16 , and the decay of circularly polarised EM waves in cold, homogeneous plasma 17 . Recently, excellent theoretical work on a warm-fluid model for magnetized LPI has been done by Shi 18 .…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the focusing nature of the UHW is highly dependent on the initial power of the laser beam, growth rate of the laser spike and the strength of the magnetic field. Laham et al (1998Laham et al ( , 2000 considered the decay of an extraordinary wave into two electrostatic waves at frequencies close to the upper hybrid frequency. They showed that the two plasmon decay growth rate decreases with increasing magnetic field.…”
Section: Introductionmentioning
confidence: 99%